Factors associated with 10 years of continuous viral load suppression on HAART. Issue 1 (December 2016) - Bello, Kathryn; Mesner, Octavio; O'Bryan, Thomas; Won, Seung; Lalani, Tahaniyat; Ganesan, Anuradha; Agan, Brian; Okulicz, Jason
Abstract Background The principal goal of HAART is sustained viral load (VL) suppression resulting in immune reconstitution and improved HIV outcomes. We studied the factors associated with 10 years of continuous VL suppression on HAART in the US Military HIV Natural History Study. Methods Participants with continuous VL suppression (CS, n  = 149) were compared to those who did not have continuous viral load suppression (NCS, n  = 127) for ≥10 years on HAART. Factors associated with >10 years of VL suppression were evaluated by multivariate logistic regression. Additionally, association between CS and CD4 reconstitution was analyzed with a mixed effects model. Results Compared to NCS participants, a lower proportion of CS participants started HAART in the early HAART era (66 vs 90 %, for years 1996–1999;p  < 0.001) and had less antiretroviral use prior to HAART (37 vs 83 %;p  < 0.001). At initial HAART, the median CD4 cell count was higher and VL was lower for CS compared to NCS participants (375 cells/uL [256, 499] vs 261 cells/uL [146, 400];p  < 0.001 and 4.4 log10 copies/mL [3.5, 4.9] vs 4.5 log10 copies/mL [3.8, 5.0];p  = 0.048, respectively). New AIDS events were lower during HAART (5 vs 13 %;p  = 0.032) and post-HAART CD4 trajectories were greater for the CS compared to NCS group. Factors negatively associated with ≥10 years of VL suppression included log10 VL at first HAART (OR 0.61, 95 % CI 0.4, 0.92;p  = 0.020) and antiretroviral use prior to HAART (OR 0.16, 95 % CI 0.06, 0.38;p  < .001). Conclusions Sustained VL suppression is a key to long-term health in HIV-infected patients, as demonstrated by the lower proportion of AIDS events observed 10 years after HAART initiation. The current use of more potent and well-tolerated regimens may mitigate the negative factors of pre-HAART VL and prior ARV use encountered by treatment initiated in the early HAART era.